A novel HLA‐B allele, B*13:18, identified by sequence‐based typing. Issue 2 (31st December 2012) - Liu, N.; Zhang, Z.; Shan, X.; Cui, S.; Zhao, B.
<x xml:space="preserve">Abstract</x> The B*13:18 allele differs from the most closely matching allele B*13:02:01 by one nucleotide substitution in exon 3, at position 539.